EVALUATION OF EFFECTIVE MECHANICAL PROPERTIES OF COMPLEX MULTIPHASE MATERIALS WITH FINITE ELEMENT METHOD - said BOUTAANI, Mohamed; MADANI, Salah; FEDAOUI, Kamel; KANIT, Toufik (U.P.B. Sci. Bull., Series D, 2017)
Prediction of effective properties for multiphase composite is very important not only to analysis and optimization of material performance, but also to new material designs. In this paper, the effective elastic property of some complex particulate composites is analyzed and compared with numerical results, demonstrating the validity of the proposed approach. We propose the equivalent morphology concept for the numerical homogenization of random composites. In this study, this concept is extended for complex material. A home script based on Python codes is made to automate the generating of Representative volume element with various volume fraction.